REPRESENTASI PERAN DAN RELASI GENDER DALAM NOVEL CANTIK ITU LUKA KARYA EKA KURNIAWAN DAN NOVEL NAYLA KARYA DJENAR MAESA AYU - Wiyatmi Wiyatmi (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2009)
This study aims to describe the representation of gender relation and gender role and Eka Kurniawan’s and Djenar Maesa Ayu’s different visions of the two. The data sources were Cantik Itu Luka, a novel by Eka Kurniawan and Nayla, a novel by Djenar Maesa Ayu. The data were analyzed by means of the qualitative descriptive technique through categorization, tabulation, and inference employing the feminist literary criticism theory. The findings are as follows. First, Cantik Itu Luka representsthe gender relation dominated by patriarchal power especially in the public domain, while Nayla represents the gender relation leading to superior women against the patriarchal power. Second, Eka Kurniawan views that men have dominant positionsin relation to women, while Djenar Maesa Ayu views that men’s domination must be opposed by presenting dominant female figures. Third, Eka Kurniawan views that patriarchal domination in gender role still cannot be opposed by women, while Djenar Maesa Ayu views that women must be able to compete with men especially in the public role.